Effect of accelerometer mass on thin plate vibration - Baharin, Nor Hatini; Abdul Rahman, Roslan (Faculty of Mechanical Engineering, 2009)

(untitled)
Generally accelerometer mass effect is ignored in experimental studies based on the assumption that the accelerometer mass is negligible compared to the mass of the test structure. However when lightweight structure is tested, this effect is significant. The purpose of this study is to investigate the effect of accelerometer mass on thin plate vibration. The natural frequency and its corresponding mode shape were the parameters of interest. The thin plate clamped free boundary condition was investigated by using experimental modal analysis and finite element analysis. The accelerometer mass was added and mounted at three different locations. Results show the accelerometer mass has significant effect on some of the modes of the structure while other modes remain unchanged. The accelerometer mounted at a point of peak deflection of the plate showed large changes of natural frequencies and its corresponding mode shapes. There are no significant changes of natural frequency and mode shapes for accelerometer attached at nodal line of the particular mode. It is concluded that, the effect of accelerometer mass depends on the location of the accelerometer, vibration mode and magnitude of accelerometer mass